High Open‐Circuit Voltage Cs2AgBiBr6 Carbon‐Based Perovskite Solar Cells via Green Processing of Ultrasonic Spray‐Coated Carbon Electrodes from Waste Tire Sources. Issue 22 (1st October 2022) - Schmitz, Fabian; Lago, Nicolò; Fagiolari, Lucia; Burkhart, Julian; Cester, Andrea; Polo, Andrea; Prato, Mirko; Meneghesso, Gaudenzio; Gross, Silvia; Bella, Federico; Lamberti, Francesco; Gatti, Teresa
Abstract: Costs and toxicity concerns are at the center of a heated debate regarding the implementation of perovskite solar cells (PSCs) into commercial products. The first bottleneck could be overcome by eliminating the top metal electrode (generally gold) and the underlying hole transporting material and substituting both with one single thick layer of conductive carbon, as in the so‐called carbon‐based PSCs (C‐PSCs). The second issue, related to the presence of lead, can be tackled by resorting to other perovskite structures based on less toxic metallic components. An interesting case is that of the double perovskite Cs2 AgBiBr6, which at present still lacks the outstanding optoelectronic performances of the lead‐based counterparts but is very stable to environmental factors. In this work, the processing of carbon electrodes onto Cs2 AgBiBr6 ‐based C‐PSCs was reported, starting from an additive‐free isopropanol ink of a carbon material obtained from the hydrothermal recycling of waste tires and employing a high‐throughput ultrasonic spray coating method in normal environmental conditions. Through this highly sustainable approach that ensures a valuable step from an end‐of‐life to an end‐of‐waste status for used tires, devices were obtained delivering a record open circuit voltage of 1.293 V, which might in the future represent ultra‐cheap solutions to power the indoor Internet of Things ecosystem. Abstract : End‐of‐waste : Waste tires are transformed into conductive carbon black for use as hole‐extracting contact in lead‐free perovskite solar cells. This carbon electrode is processed via spray‐coating from pure isopropanol with no additives, making the whole process highly sustainable. The resulting photovoltaic devices deliver a very high open‐circuit voltage due to the built‐in potential established at the perovskite/carbon interface.